FAKTOR-FAKTOR YANG MEMPENGARUHI FIRM PERFORMANCE PADA PERUSAHAAN BASIC MATERIALS YANG TERDAFTAR DI BEI - Putri Andriani Arjo; Sufiyati Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
The purpose of this research is to obtain empirical evidence the effect of human capital efficiency (HCE), structural capital efficiency (SCE), capital employed efficiency (CEE), capital, and firm size on the firm performance of 2 basic materials companies listed on the Indonesia Stock Exchange in 2019-2021. The sample selection used a purposive sampling method and 47 companies were obtained. The data processing technique uses multiple linear analysis methods with the SPSS Statistics 25 software program. The results of the study simultaneously state that human capital efficiency, structural capital efficiency, capital employed efficiency, capital structure and firm size have a simultaneous effect on firm performance. The results of the study partially stated that partially stated that capital structure and firm size had a significant effect on firm performance while human capital efficiency, structural capital efficiency, capital employed efficiency had no significant effect. The implication of this research is that companies manage their resources in order to improve company performance.